Study on effects of molecule structure on exhaust emissions from RCCI engine fueled with low alcohol isomers. (15th November 2021) - Han, Weiqiang; Fan, Zhenhua; Jin, Chao; Tang, Guoqiang; Lu, Yao; Pan, Suozhu; Zhong, Yingzi; Liu, Haifeng
Highlights: Change of emissions with molecule structure is studied based on low alcohol isomers. Real influence factors and their sequence on different emissions are analyzed. Nitrogen oxides and particle mass concentration are unrelated to molecule structure. All emissions are unrelated to hydroxyl group position. Only hydrocarbons are correlated to methyl branches. Abstract: Due to the existence of reactivity stratification in mixture of Reactivity Controlled Compression Ignition (RCCI) engine, effects of molecule structure of low alcohols on exhaust emissions may be different. Three kinds of molecule structure, hydroxyl group position (OHP), methyl branches (MB) and straight carbon chain (SCC) are constructed through propanol and butanol isomers, and experimental data of exhaust emissions were drawn from RCCI engine under different oxygen mass contents (RO ) and start of injections (SOI). Then, changes of exhaust emissions with OHP, MB, SCC, RO and SOI, and real influence factors and influence sequence of them on emissions are analyzed. The results show that: Although a certain emission changes with a certain impact factor, they may not be correlated with each other, which means the determination of real influencing factors and influence sequence is necessary. This determination is helpful to find out the strongest correlation influencing factors to optimize exhaust emissions. It is worth noting that, different emissions have different real influencing factors. NOX emission and particle mass concentration (PMC) are unrelated to molecule structure. On the contrary, they are only correlated to SOI. Moreover, all emissions are unrelated to OHP, and only HC emission is correlated to MB, while SCC is correlated to multiple emissions, and emission types correlated to Ro and SOI are the most.